NOX enzymes in the central nervous system: from signaling to disease - Sorce, Silvia; Krause, Karl-Heinz (Antioxidants & redox signaling, 2009)
Oxidative stress has been implicated in the pathogenesis of neurologic and psychiatric diseases. The brain is particularly vulnerable to oxidative damage due to high oxygen consumption, low antioxidant defense, and an abundance of oxidation-sensitive lipids. Production of reactive oxygen species (ROS) by mitochondria is generally thought to be the main cause of oxidative stress. However, a role for ROS-generating NADPH oxidase NOX enzymes has recently emerged. Activation of the phagocyte NADPH oxidase NOX2 has been studied mainly in microglia, where it plays a role in inflammation, but may also contribute to neuronal death in pathologic conditions. However, NOX-dependent ROS production can be due to the expression of other NOX isoforms, which are detected not only in microglia, but also in astrocytes and neurons. The physiologic and pathophysiologic roles of such NOX enzymes are only partially understood. In this review, we summarize the present knowledge about NOX enzymes in the central nervous system and their involvement in neurologic and psychiatric diseases.